Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Plunging into a world? A novel approach to undergraduates’ metaphors of reading - Scharlau, Ingrid; Körber, Miriam; Karsten, Andrea (Frontline Learning Research)
Although there is considerable research on and knowledge about students’ conceptual-izations of learning or academic practices and skills, the variability of these conceptu-alizations has been consistently neglected.In the present study, we address this varia-bility in the field of academic readingwith the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students’ conceptual met-aphors of reading. Ourspecific methodologicalapproach to identify the structure of these conceptual metaphorsallowsto analyze subjective agency on a lexical as well as grammatical level.The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors ina sample of 143 texts written by bachelor students.
Keywords: metaphor; conceptual metaphor; metaphor analysis; academic reading; transitivity

Welche Rolle spielen Fachkulturen heute? Bericht von einer Erkundungsstudie. - Scharlau, Ingrid; Huber, Ludwig (die hochschullehre)
With the present exploration, we aimed to answer the question whether distinct disciplinary cultures are present at today’s universities. To this purpose, we conducted 16 interviews with scholars from different disciplines. Qualitative analysis shows that disciplinary cultures in a narrow, epistemological sense (including forms of knowledge and work as well as organisation of teaching and learning) are perceived as distinct aspects of higher education and deemed important. Disciplinary cultures in a broader sense related to lifestyle and habitus, however, were hardly reported and not perceived as characteristic. Questions of social selectivity or inequality within universities were rarely touched in the interviews. Own cultures are typically described as rather heterogeneous, which is not the case for other cultures. Handling of possible cultures as well as differences by the interviewees turned out to be very cautious, at the same time restrained and respectful. Even where differences are observed or different values are revealed, there is little evidence of disputes. Consequences of these findings for research into disciplinary cultures and higher education are discussed.
Keywords: disciplinary culture; habitus; distinctions

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

Genericity in Network Dynamics - Schwenker, Sören
This thesis deals with the investigation of dynamical properties – in particular generic synchrony breaking bifurcations – that are inherent to the structure of a semigroup network as well the numerous algebraic structures that are related to these types of networks. Most notably we investigate the interplay between network dynamics and monoid representation theory as induced by the fundamental network construction in terms of hidden symmetry as introduced by RINK and SANDERS. After providing a brief survey of the field of network dynamics in Part I, we thoroughly introduce the formalism of semigroup networks, the customized dynamical systems theory, and the necessary background from monoid representation theory in Chapters 3 and 4. The remainder of Part II investigates generic synchrony breaking bifurcations and contains three major results. The first is Theorem 5.11, which shows that generic symmetry breaking steady state bifurcations in monoid equivariant dynamics occur along absolutely indecomposable subrepresentations – a natural generalization of the corresponding statement for group equivariant dynamics. Then Theorem 7.12 relates the decomposition of a representation given by a network with high-dimensional internal phase spaces to that induced by the same network with one-dimensional internal phase spaces. This result is used to show that there is a smallest dimension of internal dynamics in which all generic l-parameter bifurcations of a fundamental network can be observed (Theorem 7.24). In Part III, we employ the machinery that was summarized and further developed in Part II to feedforward networks. We propose a general definition of this structural feature of a network and show that it can equivalently be characterized in different algebraic notions in Theorem 8.35. These are then exploited to fully classify the corresponding monoid representation for any feedforward network and to classify generic synchrony breaking steady state bifurcations with one- or highdimensional internal dynamics.

Speech Processing for Digital Home Assistance: Combining Signal Processing With Deep-Learning Techniques - Haeb-Umbach, Reinhold; Watanabe, Shinji; Nakatani, Tomohiro; Bacchiani, Michiel; Hoffmeister, Bjoern; Seltzer, Michael L.; Zen, Heiga; Souden, Mehrez (IEEE Signal Processing Magazine)
Once a popular theme of futuristic science fiction or far-fetched technology forecasts, digital home assistants with a spoken language interface have become a ubiquitous commodity today. This success has been made possible by major advancements in signal processing and machine learning for so-called far-field speech recognition, where the commands are spoken at a distance from the sound capturing device. The challenges encountered are quite unique and different from many other use cases of automatic speech recognition. The purpose of this tutorial article is to describe, in a way amenable to the non-specialist, the key speech processing algorithms that enable reliable fully hands-free speech interaction with digital home assistants. These technologies include multi-channel acoustic echo cancellation, microphone array processing and dereverberation techniques for signal enhancement, reliable wake-up word and end-of-interaction detection, high-quality speech synthesis, as well as sophisticated statistical models for speech and language, learned from large amounts of heterogeneous training data. In all these fields, deep learning has occupied a critical role.

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Updatable Anonymous Credentials and Applications to Incentive Systems - Blömer, Johannes; Bobolz, Jan; Diemert, Denis Pascal; Eidens, Fabian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security - CCS '19)
In this paper, we introduce updatable anonymous credential systems (UACS) and use them to construct a new privacy-preserving incentive system. In a UACS, a user holding a credential certifying some attributes can interact with the corresponding issuer to update his attributes. During this, the issuer knows which update function is run, but does not learn the user's previous attributes. Hence the update process preserves anonymity of the user. One example for a class of update functions are additive updates of integer attributes, where the issuer increments an unknown integer attribute value v by some known value k. This kind of update is motivated by an application of UACS to incentive systems. Users in an incentive system can anonymously accumulate points, e.g. in a shop at checkout, and spend them later, e.g. for a discount.

Scaffoldingelemente zur Sprachförderung im Textilunterricht. - Stenzel, Nadja; Drumm, Sandra (ProDaZ)

Lektionen für Alexa & Co?! - Haeb-Umbach, Reinhold (DFG forschung 1/2019)
Wenn akustische Signalverarbeitung mit automatisiertem Lernen verknüpft wird: Nachrichtentechniker arbeiten mit mehreren Mikrofonen und tiefen neuronalen Netzen an besserer Spracherkennung unter widrigsten Bedingungen. Von solchen Sensornetzwerken könnten langfristig auch digitale Sprachassistenten profitieren.

Vorwort: Gender, Technik und Politik 4.0 – Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit - Weber, Jutta (Gender, Technik und Politik 4.0 – Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit, special issue of “Gender“ (Hg.: Jutta Weber/Diana Lengersdorf))

Zur Ehrenpromotion von Maria von Welser an der Fakultät für Kulturwissenschaften der Universität Paderborn - Hagengruber, Ruth (Konsens)
Keywords: Maria von Welser; Women; Media; War; Women in War; Refugees

Tagungsbericht: Musiklandschaften zwischen Pader und Rhein. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Interdisziplinäre Tagung vom 15. bis 17. Juli 2019 in Paderborn - Becker, Rieke; Lauert, Markus; Otto, Arnold

Kooperation selbst bestimmt? Interdisziplinäre Kooperation und Zielkonflikte in inklusiven Grundschulen und Förderschulen - Neumann, Phillip
Die Kooperation von Lehrkräften und Sonderpädagog_innen stellt eine zentrale Bedingung inklusiver Beschulung von Schüler_innen mit und ohne sonderpädagogische Förderbedarfe dar. Als ein maßgebliches Hemmnis der Zusammenarbeit gilt das Autonomie-Paritäts-Muster. Dieses besagt, dass Lehrkräfte aufgrund spezifischer Arbeitsbedingungen und Strukturmerkmale pädagogischer Arbeit in Schule und Unterricht ein hohes Ausmaß an Autonomie i.S.v. ‚Privatheit im Unterricht‘ anstreben. Dennoch weisen Studien darauf hin, dass Lehrkräfte und Sonderpädagog_innen dennoch intensive Kooperationsformen praktizieren und anstreben. In der Arbeit wird mit einem Rückgriff auf die Selbstbestimmungstheorie argumentiert, dass Kooperation auch mit einem hohen Autonomieerleben einhergehen kann, wenn Lehrkräfte und Sonderpädagog_innen Kooperation als Teil ihrer eigenen Professionalität internalisiert haben. Zudem werden Einflussfaktoren auf die Häufigkeit von Kooperation sowie die Wahrnehmung und Belastung von Antinomien und Zielkonflikten als Strukturmerkmale des pädagogischen Handelns untersucht. Grundlage der quantitativ-empirischen Analysen ist eine Stichprobe von insgesamt 222 Lehrkräften und Sonderpädagog_innen in inklusiven Grundschulen und Förderschulen für den Förderschwerpunkt Lernen. Als ein wesentliches Ergebnis der Arbeit zeigt sich, dass negative Effekte der Kooperation auf das Autonomieerleben ausbleiben, sodass die aufgeworfenen Zweifel an der Relevanz des Autonomie-Paritäts-Musters bestärkt werden. Darüber hinaus erweisen sich die Berufserfahrung sowie der Rückhalt der Schulleitung durch geschaffene Zeitfenster im Stundenplan als relevante Einflussfaktoren auf die Häufigkeit der Kooperation von Sonderpädagog_innen in inklusiven Grundschulen. Lehrkräfte in inklusiven Grundschulen nehmen weniger Zielkonflikte und Antinomien wahr und erleben diese weniger belastend, je häufiger sie mit Sonderpädagog_innen kooperieren. Die Ergebnisse werden hinsichtlich theoretischer Implikationen, der Professionalisierung von Lehrkräften und Sonderpädagog_innen sowie Möglichkeiten der Förderung von Kooperation und kooperativer Strukturen diskutiert.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; BiLieF; Multiprofessionelle Kooperation; Grundschule; Förderschule

Gender, Technik und Politik 4.0. Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit. Schwerpunktheft der Zeitschrift „Gender“, Jg. 11(3/19) (Gender)

Method for Analysing Requirement Change Propagation based on a Modified Pagerank Algorithm - Gräßler, Iris; Thiele, Henrik; Oleff, Christian; Scholle, Philipp; Schulze, Veronika (Proceedings of the Design Society: International Conference on Engineering Design)
Complexity of products and systems is increasing through digitalization, interdisciplinarity as well as high technology maturity and new business models. In consequence, new product development (NPD) projects need to manage and satisfy a large number of requirements from a broad range of stakeholders. Yet, NPD projects are often delayed due to requirement changes. In this paper, a new method for analyzing requirement change propagation is presented. The method is based on the assessment of requirement interrelations structured in a requirements structure matrix by a modified page-rank algorithm. By the method, a high number of strongly interrelated requirements can be analyzed in an efficient manner. Additionally, higher-level interrelations as well as the relative weights of requirements are also incorporated in the analysis. Hereby, an efficient holistic approach towards the analysis of requirement change propagation is proposed.

The Role of Saliency in Learning First Words - Wildt, Eugenia; Rohlfing, Katharina; Scharlau, Ingrid (Frontiers in Psychology)

Gemeinsam biblischen Geschichten begegnen - reziprokes Lehren als bibeldidaktische Methode - Uppenkamp, Vera; Sarah-Luise, Weßler (Miteinander am Tisch. Tische als Ort sozialer Utopien)

Teilautomatisierte Parameteridentifikation für die Validierung von Dynamikmodellen im modellbasierten Entwurf mechatronischer Systeme - Kruse, Daniel

Almost Optimal Classical Approximation Algorithms for a Quantum Generalization of Max-Cut - Gharibian, Sevag; Parekh, Ojas (Proceedings of the 22nd International Workshop on Approximation Algorithms for Combinatorial Optimization Problems (APPROX))

The complexity of simulating local measurements on quantum systems - Gharibian, Sevag; Yirka, Justin (Quantum)

Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data

Öffentlichkeit im digitalen Kapitalismus - Fuchs, Christian (Das Ende der Vielfalt? Zur Diversität der Medien)

Appropriation of Digital Machines and Appropriation of Fixed Capital as the Real Appropriation of Social Being: Reflections on Toni Negri’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

M. N. Roy and the Frankfurt School: Socialist Humanism and the Critical Analysis of Communication, Culture, Technology, Fascism and Nationalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

What is Critical Digital Social Research? Five Reflections on the Study of Digital Society - Fuchs, Christian (Journal of Digital Social Research)

We Need a Full Public Service Internet – State-Owned Infrastructure is Just the Start - Fuchs, Christian (The Conversation)

Boris Johnson Takes His Brexit Demagoguery to the Social Media Sphere - Fuchs, Christian (TruthOut)

Straightforward Immobilization of Phosphonic Acids and Phosphoric Acid Esters on Mesoporous Silica and Their Application in an Asymmetric Aldol Reaction - Weinberger, Christian; Heckel, Tatjana; Schnippering, Patrick; Schmitz, Markus; Guo, Anpeng; Keil, Waldemar; Marsmann, Heinrich C.; Schmidt, Claudia; Tiemann, Michael; Wilhelm, René (Nanomaterials)
The combined benefits of moisture-stable phosphonic acids and mesoporous silica materials (SBA-15 and MCM-41) as large-surface-area solid supports offer new opportunities for several applications, such as catalysis or drug delivery. We present a comprehensive study of a straightforward synthesis method via direct immobilization of several phosphonic acids and phosphoric acid esters on various mesoporous silicas in a Dean–Stark apparatus with toluene as the solvent. Due to the utilization of azeotropic distillation, there was no need to dry phosphonic acids, phosphoric acid esters, solvents, or silicas prior to synthesis. In addition to modeling phosphonic acids, immobilization of the important biomolecule adenosine monophosphate (AMP) on the porous supports was also investigated. Due to the high surface area of the mesoporous silicas, a possible catalytic application based on immobilization of an organocatalyst for an asymmetric aldol reaction is discussed.

Challenging algorithmic profiling: The limits of data protection and anti-discrimination in responding to emergent discrimination - Mann, Monique; Matzner, Tobias (Big Data & Society)
The potential for biases being built into algorithms has been known for some time (e.g., Friedman and Nissenbaum, 1996), yet literature has only recently demonstrated the ways algorithmic profiling can result in social sorting and harm marginalised groups (e.g., Browne, 2015; Eubanks, 2018; Noble, 2018). We contend that with increased algorithmic complexity, biases will become more sophisticated and difficult to identify, control for, or contest. Our argument has four steps: first, we show how harnessing algorithms means that data gathered at a particular place and time relating to specific persons, can be used to build group models applied in different contexts to different persons. Thus, privacy and data protection rights, with their focus on individuals (Coll, 2014; Parsons, 2015), do not protect from the discriminatory potential of algorithmic profiling. Second, we explore the idea that anti-discrimination regulation may be more promising, but acknowledge limitations. Third, we argue that in order to harness anti-discrimination regulation, it needs to confront emergent forms of discrimination or risk creating new invisibilities, including invisibility from existing safeguards. Finally, we outline suggestions to address emergent forms of discrimination and exclusionary invisibilities via intersectional and post-colonial analysis.

Gas Responsive Nanoswitch: Copper Oxide Composite for Highly Selective H2S Detection - Paul, Andrej; Schwind, Bertram; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (Advanced Functional Materials)
A nanocomposite material based on copper(II) oxide (CuO) and its utilization as a highly selective and stable gas-responsive electrical switch for hydrogen sulphide (H2S) detection is presented. The material can be applied as a sensitive layer for H2S monitoring, e.g., in biogas gas plants. CuO nanoparticles are embedded in a rigid, nanoporous silica (SiO2) matrix to form an electrical percolating network of low conducting CuO and, upon exposure to H2S, highly conducting copper(II) sulphide (CuS) particles. By steric hindrance due to the silica pore walls, the structure of the network is maintained even though the reversible reaction of CuO to CuS is accompanied by significant volume expansion. The conducting state of the percolating network can be controlled by a variety of parameters, such as temperature, electrode layout, and network topology of the porous silica matrix. The latter means that this new type of sensing material has a structure-encoded detection limit for H2S, which offers new application opportunities. The fabrication process of the mesoporous CuO@SiO2 composite as well as the sensor design and characteristics are described in detail. In addition, theoretical modeling of the percolation effect by Monte-Carlo simulations yields deeper insight into the underlying percolation mechanism and the observed response characteristics.

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Mary (Tekniikan Waiheita)

Quasiparticle and excitonic effects in the optical response of KNbO3 - Schmidt, Falko; Riefer, Arthur; Schmidt, Wolf Gero; Schindlmayr, Arno; Imlau, Mirco; Dobener, Florian; Mengel, Nils; Chatterjee, Sangam; Sanna, Simone (Physical Review Materials)
The cubic, tetragonal, and orthorhombic phase of potassium niobate (KNbO3) are studied based on density-functional theory. Starting from the relaxed atomic geometries, we analyze the influence of self-energy corrections on the electronic band structure within the GW approximation. We find that quasiparticle shifts widen the direct (indirect) band gap by 1.21 (1.44), 1.58 (1.55), and 1.67 (1.64) eV for the cubic, tetragonal, and orthorhombic phase, respectively. By solving the Bethe-Salpeter equation, we obtain the linear dielectric function with excitonic and local-field effects, which turn out to be essential for good agreement with experimental data. From our results, we extract an exciton binding energy of 0.6, 0.5, and 0.5 eV for the cubic, tetragonal, and orthorhombic phase, respectively. Furthermore, we investigate the nonlinear second-harmonic generation (SHG) both theoretically and experimentally. The frequency-dependent second-order polarization tensor of orthorhombic KNbO3 is measured for incoming photon energies between 1.2 and 1.6 eV. In addition, calculations within the independent-(quasi)particle approximation are performed for the tetragonal and orthorhombic phase. The novel experimental data are in excellent agreement with the quasiparticle calculations and resolve persistent discrepancies between earlier experimental measurements and ab initio results reported in the literature.

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Beyond Big Data Capitalism, Towards Dialectical Digital Modernity: Reflections on David Chandler’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Introduction: Big Data Capitalism – Politics, Activism, and Theory - Fuchs, Christian; Chandler, David (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Slow Media: How to Renew Debate in the Age of Digital Authoritarianism - Fuchs, Christian (The Conversation)

Henry A. Giroux and the Culture of Neoliberal Fascism - Fuchs, Christian (Los Angeles Review of Books)

The Human is Dead, Long Live the Algorithm!. Human-Algorithmic Ensembles and Liberal Subjectivity - Matzner, Tobias (Theory, Culture & Society)
The article analyzes the relation of humans and technology concerning so called ‘intelligent’ or ‘autonomous’ algorithms that are applied in everyday contexts but are far removed from any form of substantial artificial intelligence. In particular, the use of algorithms in surveillance and in architecture is discussed. These examples are structured by a particular combination of continuity and difference between humans and technology. The article provides a detailed analysis of boundary practices that establish continuity and oppositions between humans and information technology, referring to their exemplary depiction in movies. Both strands of boundary practices have the potential to challenge as well as sustain the position of the human as liberal, autonomous subject. Finally, it is shown how the particular combination of continuity and difference that structures the use of algorithms maintains the power of liberal, autonomous subject positions, while the shift of decisions to the algorithms seems to decenter the human.

Privacy - Matzner, Tobias; Ochs, Carsten (Internet Policy Review)

Mediale und soziale Bedingtheit der Subjekte des Privaten – ein Versuch mit Hannah Arendt - Matzner, Tobias (Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Proof-Carrying Hardware Versus the Stealthy Malicious LUT Hardware Trojan - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Applied Reconfigurable Computing)
Reconfigurable hardware has received considerable attention as a platform that enables dynamic hardware updates and thus is able to adapt new configurations at runtime. However, due to their dynamic nature, e.g., field-programmable gate arrays (FPGA) are subject to a constant possibility of attacks, since each new configuration might be compromised. Trojans for reconfigurable hardware that evade state-of-the-art detection techniques and even formal verification, are thus a large threat to these devices. One such stealthy hardware Trojan, that is inserted and activated in two stages by compromised electronic design automation (EDA) tools, has recently been presented and shown to evade all forms of classical pre-configuration detection techniques. This paper presents a successful pre-configuration countermeasure against this ``Malicious Look-up-table (LUT)''-hardware Trojan, by employing bitstream-level Proof-Carrying Hardware (PCH). We show that the method is able to alert innocent module creators to infected EDA tools, and to prohibit malicious ones to sell infected modules to unsuspecting customers.

VimaS_num: Measuring situational perception in mathematics of early childhood teachers - Bruns, Julia; Gasteiger, Hedwig (Proceedings of the 43rd Conference of the International Group for the Psychology of Mathematics Education)

Mathematikdidaktischen Wissen von frühpädagogischen Fachkräften aus kognitiv-situationsbezogener Perspektive – Theoretisches Konstrukt und empirische Erfassung - Bruns, Julia; Gasteiger, Hedwig (Beiträge zum Mathematikunterricht 2019)

Implementing a Real-time System on a Platform FPGA operated with ReconOS - Lienen, Christian

Federal Judge Ideology: A New Measure of Ex Ante Litigation Risk - HUANG, ALLEN; HUI, KAI WAI; Li, Reeyarn (Journal of Accounting Research)
ABSTRACT Drawing on the political theory of judicial decision making, our paper proposes a new and parsimonious ex ante litigation risk measure: federal judge ideology. We find that judge ideology complements existing measures of litigation risk based on industry membership and firm characteristics. Firms in liberal circuits (the third quartile in ideology) are 33.5% more likely to be sued in securities class action lawsuits than those in conservative circuits (the first quartile in ideology). This result is stronger after the U.S. Supreme Court's ruling in the Tellabs case. We next show that the effect of judge ideology on litigation risk is greater for firms with more sophisticated shareholders and with higher expected litigation costs. Furthermore, judicial appointments affect litigation risk and the value of firms in the circuit, highlighting the economic consequences of political appointments of judges. Finally, using our new measure, we document that litigation risk deters managers from providing long‐term earnings guidance, a result that existing measures of litigation risk cannot show.
Keywords: Economics and Econometrics; Finance; Accounting

Remaining useful lifetime prediction based on adaptive failure thresholds - Bender, Amelie; Schinke, Lennart; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
Remaining useful lifetime (RUL) predictions as part of a condition monitoring system are focused in more and more research and industrial applications. To establish an efficient and precise estimate of the RUL of a technical product, different uncertainties have to be handled. To minimize the uncertainties of the RUL estimation, a reliable and accurate prognostic approach as well as a good failure threshold are important. Regarding the failure threshold, most often an expert sets a fixed failure threshold. However, neither the a priori known failure threshold nor a fixedthreshold value are feasible in every application. Especially in the case of varying characteristics of the monitored system, an adaptive failure threshold is of great importance concerning the accuracy of the RUL estimation. Rubber-metal-elements, which are used in a wide range of applications for vibration and sound isolation, are mon-itored by thermocouples to allow for lifetime predictions. Therefore, the element’s state is described by its temper-ature during its service life. Aiming to establish accurate RUL predictions of a rubber-metal-element, uncertainties due to nonlinear material characteristics and changing operational conditions have to be considered. Consequently, different temperature-based failure threshold definitions are implemented and compared within a particle filtering approach.
Keywords: RUL prediction; adaptive threshold; prognostics; condition monitoring

FPGAs im Rechenzentrum - Platzner, Marco; Plessl, Christian (Informatik Spektrum)

Digital Twin for Reliability Analysis During Design and Operation of Mechatronic Systems - Kaul, Thorben; Bender, Amelie; Sextro, Walter (Proceedings of the 29th European Safety and Reliability Conference (ESREL2019))
As the emerging digitalization of technical systems offers immense opportunities to be exploited by means of bigdata analysis, ubiquitous computing and largely networked systems, the digital twin comes into focus to combineall these aspects to an attendant model of an individual system during design phase as well as during operation.Since state-of-art technical systems are growing increasingly complex due to inherent intelligence and increasingfunctionality, i. e. autonomous behavior so far, it becomes considerably challenging to ensure reliability for thosesystems. Many methods were developed to support a reliability focused design or reliability-by-design approachesto tackle this challenge during design process. In field, data-based methods, i. e. condition monitoring enabled bythe rise of machine learning approaches, are exploited to ensure a reliable operation based on the current conditionof the monitored system. In order to take advantage of existing models of system reliability during design phaseand condition monitoring systems during operation, a method is proposed to combine both approaches in order toset up a digital twin with focus on system reliability. The base model of the digital twin is taken from the systemreliability model from the design phase and is used during operation and therein updated to the current reliabilitybased on the state estimation of the condition monitoring system. The approach is illustrated with a case study of arolling bearing test rig.

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Second harmonic microscopy of poled x-cut thin film lithium niobate: Understanding the contrast mechanism - Rüsing, Michael; Zhao, J.; Mookherjea, S. (Journal of Applied Physics)
Thin film lithium niobate has been of great interest recently, and an understanding of periodically poled thin films is crucial for both fundamental physics and device developments. Second-harmonic (SH) microscopy allows for the noninvasive visualization and analysis of ferroelectric domain structures and walls. While the technique is well understood in bulk lithium niobate, SH microscopy in thin films is largely influenced by interfacial reflections and resonant enhancements, which depend on film thicknesses and substrate materials. We present a comprehensive analysis of SH microscopy in x-cut lithium niobate thin films, based on a full three-dimensional focus calculation and accounting for interface reflections. We show that the dominant signal in backreflection originates from a copropagating phase-matched process observed through reflections, rather than direct detection of the counterpropagating signal as in bulk samples. We simulate the SH signatures of domain structures by a simple model of the domain wall as an extensionless transition from a −χ(2) to a +χ(2) region. This allows us to explain the main observation of domain structures in the thin-film geometry, and, in particular, we show that the SH signal from thin poled films allows to unambiguously distinguish areas, which are completely or only partly inverted in depth.
Keywords: General Physics and Astronomy

Leitfaden zur Gestaltung von Zugängen - Meusel, Sarah; Abendroth, Sonja; Hoeft, Maike; Albers, Timm

Unsupervised Learning of a Disentangled Speech Representation for Voice Conversion - Gburrek, Tobias; Glarner, Thomas; Ebbers, Janek; Haeb-Umbach, Reinhold; Wagner, Petra (Proc. 10th ISCA Speech Synthesis Workshop)
This paper presents an approach to voice conversion, whichdoes neither require parallel data nor speaker or phone labels fortraining. It can convert between speakers which are not in thetraining set by employing the previously proposed concept of afactorized hierarchical variational autoencoder. Here, linguisticand speaker induced variations are separated upon the notionthat content induced variations change at a much shorter timescale, i.e., at the segment level, than speaker induced variations,which vary at the longer utterance level. In this contribution wepropose to employ convolutional instead of recurrent networklayers in the encoder and decoder blocks, which is shown toachieve better phone recognition accuracy on the latent segmentvariables at frame-level due to their better temporal resolution.For voice conversion the mean of the utterance variables is re-placed with the respective estimated mean of the target speaker.The resulting log-mel spectra of the decoder output are used aslocal conditions of a WaveNet which is utilized for synthesis ofthe speech waveforms. Experiments show both good disentan-glement properties of the latent space variables, and good voiceconversion performance.

Convolutional Recurrent Neural Network and Data Augmentation for Audio Tagging with Noisy Labels and Minimal Supervision - Ebbers, Janek; Haeb-Umbach, Reinhold (DCASE2019 Workshop, New York, USA)
In this paper we present our audio tagging system for the DCASE 2019 Challenge Task 2. We propose a model consisting of a convolutional front end using log-mel-energies as input features, a recurrent neural network sequence encoder and a fully connected classifier network outputting an activity probability for each of the 80 considered event classes. Due to the recurrent neural network, which encodes a whole sequence into a single vector, our model is able to process sequences of varying lengths. The model is trained with only little manually labeled training data and a larger amount of automatically labeled web data, which hence suffers from label noise. To efficiently train the model with the provided data we use various data augmentation to prevent overfitting and improve generalization. Our best submitted system achieves a label-weighted label-ranking average precision (lwlrap) of 75.5% on the private test set which is an absolute improvement of 21.7% over the baseline. This system scored the second place in the teams ranking of the DCASE 2019 Challenge Task 2 and the fifth place in the Kaggle competition “Freesound Audio Tagging 2019” with more than 400 participants. After the challenge ended we further improved performance to 76.5% lwlrap setting a new state-of-the-art on this dataset.

Weakly Supervised Sound Activity Detection and Event Classification in Acoustic Sensor Networks - Ebbers, Janek; Drude, Lukas; Haeb-Umbach, Reinhold; Brendel, Andreas; Kellermann, Walter (CAMSAP 2019, Guadeloupe, West Indies)
In this paper we consider human daily activity recognition using an acoustic sensor network (ASN) which consists of nodes distributed in a home environment. Assuming that the ASN is permanently recording, the vast majority of recordings is silence. Therefore, we propose to employ a computationally efficient two-stage sound recognition system, consisting of an initial sound activity detection (SAD) and a subsequent sound event classification (SEC), which is only activated once sound activity has been detected. We show how a low-latency activity detector with high temporal resolution can be trained from weak labels with low temporal resolution. We further demonstrate the advantage of using spatial features for the subsequent event classification task.

Privacy-preserving Variational Information Feature Extraction for Domestic Activity Monitoring Versus Speaker Identification - Nelus, Alexandru; Ebbers, Janek; Haeb-Umbach, Reinhold; Martin, Rainer (INTERSPEECH 2019, Graz, Austria)
In this paper we highlight the privacy risks entailed in deep neural network feature extraction for domestic activity monitoring. We employ the baseline system proposed in the Task 5 of the DCASE 2018 challenge and simulate a feature interception attack by an eavesdropper who wants to perform speaker identification. We then propose to reduce the aforementioned privacy risks by introducing a variational information feature extraction scheme that allows for good activity monitoring performance while at the same time minimizing the information of the feature representation, thus restricting speaker identification attempts. We analyze the resulting model’s composite loss function and the budget scaling factor used to control the balance between the performance of the trusted and attacker tasks. It is empirically demonstrated that the proposed method reduces speaker identification privacy risks without significantly deprecating the performance of domestic activity monitoring tasks.

Die Antwerpener Börse - Aufstieg, Niedergang und Wandel (VIDEO) - Huybrechts, Yves

Tätigkeitsbericht 2007-2017 der Stabsstelle Bildungsinnovationen und Hochschuldidaktik der Universität Paderborn - Neiske, Iris; Vöing, Nera (Personal- und Organisationsentwicklung Forum für Führung, Moderation, Training, Programm-Organisation in Einrichtungen der Lehre und Forschung)

Kurz berichtet. Das E-Tutoren-Programm an der UPB. - Neiske, Iris (Paderborner Universitätszeitschrift (puz))

How ideas come into being: Tracing intertextual moments in grades of objectification and publicness - Karsten, Andrea; Bertau, Marie-Cécile (Frontiers in Psychology)
How do ideas come into being? Our contribution takes its starting point in an observation we made in empirical data from a prior study. The data center around an instant of an academic writer’s thinking during the revision of a scientific paper. Through a detailed discourse-oriented micro-analysis, we zoom in on the writer’s thinking activity and uncover the genesis of a complex idea through a sequence of interrelated moments. These moments feature different degrees of “crystallization” of the idea; from gestures, a sketch, a short written note, oral explanations to a final spelled-out written argument. For this contribution, we re-analyze the material, asking how the idea gets formed during the thinking process and how it reaches a tangible form, which is understandable both for the thinker and for other persons. We root our analysis in a notion of language as social, embodied, and dialogical activity, drawing on concepts from Humboldt, Jakubinskij, and Vygotsky. We focus our analysis on three conceptual nodes. The first node is the ebbing and advancing of language in idea formation – observable as a trajectory through linguistically more condensed or more expanded utterance forms. The second node is the degree of objectification that the idea reaches when it is performed differently in a variety of addressivity constellations, i.e., whether and how it becomes understandable to the thinker and to others in the social sphere. Finally, the third node is the saturation of the idea through what we call intrapersonal intertextuality, i.e., its complex and dialogically related re-articulations in a sequence of formative moments. With these considerations, we articulate a clear consequence for theorizing thinking. We hold that thinking is social, embodied, and dialogically organized because it is entangled with language. Ideas come into being and become understandable and communicable to other persons only by and within their different, yet, intertextually related formations.
Keywords: idea formation; language activity; objectification; intrapersonal intertextuality; articulation; Jakubinskij; Vygotsky; Humboldt

Wie groß ist ein Neutronenstern? Elementarisierende Überlegungen und Abschätzungen - Hohmann, Sascha (PhyDid B)

Investment Timing Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren (Journal of Business Economics)
We analyze the impact of wealth taxes on investment timing decisions under uncertainty and irreversibility by employing a real options model of the Dixit/Pindyck type. Considering that wealth taxes have been (re-)introduced or are under discussion in many countries, investors need decision rules for tax systems with wealth taxation. We integrate different valuation methods for wealth tax purposes, distinguish between broadly and narrowly defined wealth taxes and vary the wealth tax rate to ascertain which wealth tax design is more or less likely to accelerate or delay investment. Our main findings are threefold. First, historical cost valuation reduces the distortive timing effects of wealth taxation compared to fair value accounting. Second, broadening the wealth tax base tends to accelerate investment during high interest rate periods and delay investment during low interest rate periods. Our results predict that wealth taxes with a broad tax base are likely to discourage risky investment in times of near-zero interest rates. These distortive wealth tax base effects, however, can be avoided by granting sufficiently high depreciation deductions for wealth tax purposes. Third, the investment timing effects of wealth tax rate variations are very sensitive to the riskiness of the underlying investment. Moreover, investment timing effects crucially depend upon the depreciation rate for wealth tax purposes. A tax legislator who aims to encourage risk taking should introduce generous depreciation deductions. Our study indicates that if a wealth tax is considered to be politically inevitable, possible harmful investment effects can be mitigated by choosing appropriate valuation methods and parameters.

New Quick And Easy Publication - Will be edited by LibreCat team

“Self-Knowledge and Varieties of Human Excellence in the French Moralists.” - Blank, Andreas (British Journal for the History of Philosophy)

Erziehungswissenschaft als Verunsicherungswissenschaft. Nicht nur eine Kritik des Mobilitätsimperativs - Haker, Christoph; Otterspeer, Lukas (Debatte. Beiträge zur Erwachsenenbildung)
Sebastian Zicks erziehungswissenschaftliche Kritik des Mobilitätsimperativs ist Ausgangspunkt unseres Beitrags. Wir greifen diese Kritik auf, indem wir sie in zweifacher Hinsicht ergänzen: Erstens um einen Fokus auf soziale Mobilität, welche sich in Mobilitätsnarrativen mit räumlicher Mobilität als verwoben zeigt. Zweitens um die Perspektive auf Mobilität als Rückkehr, die wir von einer Perspektive auf Mobilität als Fortbewegung abgrenzen. Die Rückwärtsbewegung ist für uns eng an (Selbst-)Reflexionen und transformatorische Bildungsprozesse gebunden, wie sie in Didier Eribons autosozioanalytischem Vorhaben einer Rückkehr zu erkennen sind. Unsere Ausführungen münden erstens in einer Kritik am Imperativ des Bildungsaufstiegs, in dem mehr Bildung scheinbar immer mit individuellen und kollektiven Fortschritten einhergeht. Zweitens wenden wir die von uns herausgearbeitete Kritik reflexiv auf die Erziehungswissenschaft. Sie ist dann eine Verunsicherungswissenschaft, für die die Rückkehr, und damit das Hinterfragen eigener Selbstverständlichkeiten, konstitutiv ist.
Keywords: Rehabilitation; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Empirische Bildungsforschung im Wirbel unmittelbarer Rezeption - Otterspeer, Lukas; Haker, Christoph (Zeitschrift für Pädagogik)

Digitalisierung im organisierten Sport – Eine Analyse zur Nutzung digitaler Instrumente in Sportvereinen - Riedl, Lars; Ehnold, Peter; Schlesinger, Torsten (Sciamus - Sport und Management, 4)
Trotz hoher Aktualität und steigender Bedeutung liegen zum Thema Digitalisierung im Sportverein bisher kaum empirische Erkenntnisse vor. Der vorliegende Beitrag setzt sich mit folgenden Fragestellungen auseinander: (i) In welchem Umfang und zu welchem Zweck nutzen Sportvereine digitale Instrumente? (ii) Welche vereinsspezifischen Faktoren determinieren das jeweilige Nutzungsverhalten? Hierzu wurde eine Stichprobe von n=787 Sportvereinen aus Österreich und Deutschland generiert. Es zeigt sich, dass digitale Instrumente vor allem zur internen und externen Kommunikation sowie zur Bewältigung klassischer Verwaltungsaufgaben eingesetzt werden. Das Ausmaß der Nutzung hängt einerseits von vereinsexternen Bedingungen ab. So zeigt sich dahingehend ein Ländereffekt, dass in Deutschland digitale Instrumente stärker genutzt werden als in Österreich. Darüber hinaus haben Auflagen seitens der Verbände zur Verwendung bestimmter Software (z.B. für die Meldung von Wettkampfergebnissen) einen wichtigen Einfluss. Andererseits bestimmen vereinsinterne Faktoren wesentlich das Nutzungsverhalten. Positiv wirken vor allem die Vereinsziele ‚Engagement/Erfolg im Leistungssport‘ und ‚Wollen Vorreiterrolle bei der Digitalisierung einnehmen‘. Negativ wirken eine fehlende Strategie im Umgang mit digitalen Instrumenten sowie die Einschätzung, dass digitale Prozesse nicht zur eigenen Vereinskultur passen.

Zwischen Komposition, Aufführung und Herausgabe - Ried, Dennis (Mitteilungen der IMRG)

Art. ‚Lernumgebung / vorbereiteter Klassenraum‘ - Hoyer, Isabelle; Reis, Oliver (Das Wissenschaftlich-Religionspädagogische Lexikon (WiReLex))

IASPM D-A-CH. Current issues and perspectives - Flath, Beate (IASPM Journal)

Pop music festivals and (cultural) policies (IASPM Journal)

Digitale Transformation in der zivilen Gefahrenabwehr - Schultz, Andreas Maximilian; Sauerland, Torben; Werner, Thomas; Rammert, Sebastian; Habig, Therese; Marterer, Robin; Scheuermann, Lars

(WIP) Towards the Automated Composition of Machine Learning Services - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke; Faez, Amin (SCC)

Generating Resource and Performance Models for Service Function Chains: The Video Streaming Case - Dräxler, Sevil; Peuster, Manuel; Illian, Marvin; Karl, Holger (4th IEEE International Conference on Network Softwarization (NetSoft 2018))
Understanding the behavior of the components of service function chains (SFCs) in different load situations is important for efficient and automatic management and orches- tration of services. For this purpose and for practical research in network function virtualization in general, there is a great need for benchmarks and experimental data. In this paper, we describe our experiments for characterizing the relationship between resource demands of virtual network functions (VNFs) and the expected performance of the SFC, considering the individual performance of the VNFs as well as the interdependencies among VNFs within the SFC. We have designed our experiments focusing on video streaming, an important application in this context. We present examples of models for predicting the interdependence between resource demands and performance characteristics of SFCs using support vector regression and polynomial regression models. We also show practical evidence from our experiments that VNFs need to be benchmarked in their final chain setup, rather than individually, to capture important interdependencies that affect their performance. The data gathered from our experiments is publicly available.

Scaling and Placing Bidirectional Services with Stateful Virtual and Physical Network Functions - Dräxler, Sevil; Schneider, Stefan Balthasar; Karl, Holger (4th IEEE International Conference on Network Softwarization (NetSoft 2018))
Network function virtualization requires scaling and placement, deciding the number and the location of function instances. Current approaches are limited in flexibility and practical applicability. Specifically, we study dynamic, single-step, joint scaling and placement of network services with bidirectional flows traversing Physical or Virtual Network Functions (VNFs) and returning to their sources. We develop models to support stateful components and legacy network functions with fixed locations in these network services as well as the possibility of reusing VNFs across network services. We formalize the problem of jointly scaling and placing such network services as a mixed- integer linear program (MILP). We show that this problem is NP-complete and also present a heuristic algorithm to find good solutions in short time. In an extensive evaluation with realistic scenarios, we investigate the capabilities of the two approaches.

5G OS: Control and Orchestration of Services on Multi-Domain Heterogeneous 5G Infrastructures - Dräxler, Sevil; Karl, Holger; Razzaghi Kouchaksaraei, Hadi; Machwe, Azahar; Dent-Young, Crispin; Katsalis, Kostas; Samdanis, Konstantinos (27th European Conference on Networks and Communications (EUCNC 2018))

Towards Predicting Resource Demands and Performance of Distributed Cloud Services - Dräxler, Sevil; Peuster, Manuel; Illian, Marvin; Karl, Holger
Understanding the behavior of distributed cloud service components in different load situations is important for efficient and automatic management and orchestration of these services. For this purpose and for practical research in distributed cloud computing in general, there is need for benchmarks and experimental data. In this paper, we describe our experiments for characterizing the relationship between resource demands of application components and the expected performance of applica- tions. We present initial results for predicting the interdependence between resource demands and performance characteristics using support vector regression and polynomial regression models. The data gathered from our experiments is publicly available.

Kompetenzorientierte, universitäre Laborpraktika - Das Paderborner Physik Praktikum (3P) - Bauer, Anna; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Operationalisierung der experimentellen Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Qualitätsvoller Chemie- und Physikunterricht – normative und empirische Dimensionen)

Programmatic Task Network Planning - Mohr, Felix; Lettmann, Theodor; Hüllermeier, Eyke; Wever, Marcel Dominik (Proceedings of the 1st ICAPS Workshop on Hierarchical Planning)

Practical, Anonymous, and Publicly Linkable Universally-Composable Reputation Systems - Blömer, Johannes; Eidens, Fabian; Juhnke, Jakob (Topics in Cryptology - CT-RSA 2018 - The Cryptographers' Track at the RSA Conference 2018, Proceedings)

On-The-Fly Service Construction with Prototypes - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke (SCC)

Programmable and Flexible Management and Orchestration of Virtualized Network Functions - Razzaghi Kouchaksaraei, Hadi; Dräxler, Sevil; Peuster, Manuel; Karl, Holger (2018 European Conference on Networks and Communications (EuCNC))
Supporting the vast variety of network services’ management and orchestration requirements is one of the main challenges that Network Function Virtualization (NFV) is dealing with. While general management requirements such as Virtual Network Function (VNF) resource requirements can be specified by the service developers using service descriptors, specific management operations like VNF-specific configuration cannot be performed by these descriptors. On the other hand, it is inefficient and also very challenging for Management and Orchestration (MANO) frameworks to provide all specific-management operations for every individual network service and their constituent VNFs. To mitigate this issue, we propose the use of service-specific programs called Specific Managers (SMs) that can customize management and orchestration of network services and also extend the capability of MANO frameworks to support per-service management and orchestration. The results of our evaluation show that the higher flexibility and programmability enabled by SMs improve the performance of the service performance and also utilises the service provider resources more efficiently.

Pishahang: Joint Orchestration of Network Function Chains and Distributed Cloud Applications - Razzaghi Kouchaksaraei, Hadi; Dierich, Tobias; Karl, Holger
Developing cloud applications using a microservice architecture allows their functional blocks to be distributed and deployed on multiple Cloud infrastructures. This enables service providers to mix and match Cloud-based microservices and Virtual Network Functions (VNFs) that are provided by Network Function Virtualization (NFV). Provisioning complex services containing VNFs and Cloud-based microservices across NFV and cloud infrastructures can enhance service quality, reduce latency, and optimise cost. This can be provided by an orchestration system that can handle cross-ecosystem dependencies. To this end, we implemented Pishahang that is a framework for jointly managing and orchestrating virtual network functions and Cloud-based microservices. During the demo, we deploy several complex services to demonstrate features provided by Pishahang to support management and orchestration of complex services.

Fully-Featured Anonymous Credentials with Reputation System - Bemmann, Kai; Blömer, Johannes; Bobolz, Jan; Bröcher, Henrik; Diemert, Denis Pascal; Eidens, Fabian; Eilers, Lukas; Haltermann, Jan Frederik; Juhnke, Jakob; Otour, Burhan; Porzenheim, Laurens Alexander; Pukrop, Simon; et al. (Proceedings of the 13th International Conference on Availability, Reliability and Security - ARES '18)
We present CLARC (Cryptographic Library for Anonymous Reputation and Credentials), an anonymous credentials system (ACS) combined with an anonymous reputation system. Using CLARC, users can receive attribute-based credentials from issuers. They can efficiently prove that their credentials satisfy complex (access) policies in a privacy-preserving way. This implements anonymous access control with complex policies. Furthermore, CLARC is the first ACS that is combined with an anonymous reputation system where users can anonymously rate services. A user who gets access to a service via a credential, also anonymously receives a review token to rate the service. If a user creates more than a single rating, this can be detected by anyone, preventing users from spamming ratings to sway public opinion. To evaluate feasibility of our construction, we present an open-source prototype implementation.

Let the state follow its flows: An SDN-based flow handover protocol to support state migration - Peuster, Manuel; Küttner, Hannes; Karl, Holger (4th IEEE International Conference on Network Softwarization (NetSoft 2018))
Dynamically steering flows through virtualized net- work function instances is a key enabler for elastic, on-demand deployments of virtualized network functions. This becomes par- ticular challenging when stateful functions are involved, necessi- tating state management. The problem with existing solutions is that they typically embrace state migration and flow rerouting jointly, imposing a huge set of requirements on the on-boarded VNFs, e.g., solution-specific state management interfaces. In this paper, we introduce the seamless handover proto- col (SHarP). It provides an easy-to-use, loss-less, and order- preserving flow rerouting mechanism that is not fixed to a single state management approach. This allows VNF vendors to implement or use the state management solution of their choice. SHarP supports these solutions with additional information when flows are migrated. Further, we show how SHarP significantly reduces the buffer usage at a central (SDN) controller, which is a typical bottleneck in existing solutions. Our experiments show that SHarP uses a constant amount of controller buffer, irrespective of the time taken to migrate the VNF state.

Containernet 2.0: A Rapid Prototyping Platform for Hybrid Service Function Chains - Peuster, Manuel; Kampmeyer, Johannes; Karl, Holger (4th IEEE International Conference on Network Softwarization (NetSoft 2018))
Developing a virtualized network service does not only involve the implementation and configuration of the network functions it is composed of but also its integration and test with management solutions that will control the service in its production environment. These integration tasks require testbeds that offer the needed network function virtualization infrastructure~(NFVI), like OpenStack, introducing a lot of management and maintenance overheads. Such testbed setups become even more complicated when the multi point-of-presence~(PoP) case, with multiple infrastructure installations, is considered. In this demo, we showcase an emulation platform that executes containerized network services in user-defined multi-PoP topologies. The platform does not only allow network service developers to locally test their services but also to connect real-world management and orchestration solutions to the emulated PoPs. During our interactive demonstration we focus on the integration between the emulated infrastructure and state-of-the-art orchestration solutions like SONATA or OSM.

Emulation-based Smoke Testing of NFV Orchestrators in Large Multi-PoP Environments - Peuster, Manuel; Marchetti, Michael; Garcia de Blas, Gerado; Karl, Holger (European Conference on Networks and Communications (EuCNC))
Management and orchestration~(MANO) systems are the key components of future large-scale NFV environments. They will manage resources of hundreds or even thousands of NFV infrastructure installations, so called points of presence~(PoP). Such scenarios need to be automatically tested during the development phase of a MANO system. This task becomes very challenging because large-scale NFV testbeds are hard to maintain, too expensive, or simply not available. In this paper, we present a multi-PoP NFV infrastructure emulation platform that enables automated, large-scale testing of MANO stacks. We show that our platform can easily emulate hundreds of PoPs on a single physical machine and reduces the setup time of a test PoP by a factor of 232x compared to a DevStack-based test PoP installation. Further, we present a case study in which we test ETSI's Open Source MANO~(OSM) against our proposed system to gain insights about OSM's behaviour in large-scale NFV deployments.

ML-Plan: Automated Machine Learning via Hierarchical Planning - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke (Machine Learning)
Automated machine learning (AutoML) seeks to automatically select, compose, and parametrize machine learning algorithms, so as to achieve optimal performance on a given task (dataset). Although current approaches to AutoML have already produced impressive results, the field is still far from mature, and new techniques are still being developed. In this paper, we present ML-Plan, a new approach to AutoML based on hierarchical planning. To highlight the potential of this approach, we compare ML-Plan to the state-of-the-art frameworks Auto-WEKA, auto-sklearn, and TPOT. In an extensive series of experiments, we show that ML-Plan is highly competitive and often outperforms existing approaches.
Keywords: AutoML; Hierarchical Planning; HTN planning; ML-Plan

Reduction Stumps for Multi-Class Classification - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke (Proceedings of the Symposium on Intelligent Data Analysis)

Oblique incidence of semi-guided planar waves on slab waveguide steps: effects of rounded edges - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
Oblique propagation of semi-guided waves across slab waveguide structures with bent corners is investigated. A critical angle can be defined beyond which all radiation losses are suppressed. Additionally an increase of the curvature radius of the bends also leads to low-loss configurations for incidence angles below that critical angle. A combination of two bent corner systems represents a step-like structure, behaving like a Fabry-Perot interferometer, with two partial reflectors separated by the vertical height between the horizontal slabs. We numerically analyse typical high-index-contrast Si/SiO2 structures for their reflectance and transmittance properties. When increasing the curvature radius the resonant effect becomes less relevant such that full transmittance is reached with less critical conditions on the vertical distance or the incidence angle. For practical interest 3-D problems are considered, where the structures are excited by the fundamental mode of a wide, shallow rib waveguide. High transmittance levels can be observed also for these 3-D configurations depending on the width of the rib.
Keywords: tet_topic_waveguide

ML-Plan for Unlimited-Length Machine Learning Pipelines - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (ICML 2018 AutoML Workshop)
In automated machine learning (AutoML), the process of engineering machine learning applications with respect to a specific problem is (partially) automated. Various AutoML tools have already been introduced to provide out-of-the-box machine learning functionality. More specifically, by selecting machine learning algorithms and optimizing their hyperparameters, these tools produce a machine learning pipeline tailored to the problem at hand. Except for TPOT, all of these tools restrict the maximum number of processing steps of such a pipeline. However, as TPOT follows an evolutionary approach, it suffers from performance issues when dealing with larger datasets. In this paper, we present an alternative approach leveraging a hierarchical planning to configure machine learning pipelines that are unlimited in length. We evaluate our approach and find its performance to be competitive with other AutoML tools, including TPOT.
Keywords: automated machine learning; complex pipelines; hierarchical planning

JASPER: Joint Optimization of Scaling, Placement, and Routing of Virtual Network Services - Dräxler, Sevil; Karl, Holger; Mann, Zoltan Adam (IEEE Transactions on Network and Service Management)
To adapt to continuously changing workloads in networks, components of the running network services may need to be replicated (scaling the network service) and allocated to physical resources (placement) dynamically, also necessitating dynamic re-routing of flows between service components. In this paper, we propose JASPER, a fully automated approach to jointly optimizing scaling, placement, and routing for complex network services, consisting of multiple (virtualized) components. JASPER handles multiple network services that share the same substrate network; services can be dynamically added or removed and dynamic workload changes are handled. Our approach lets service designers specify their services on a high level of abstraction using service templates. JASPER automatically makes scaling, placement and routing decisions, enabling quick reaction to changes. We formalize the problem, analyze its complexity, and develop two algorithms to solve it. Extensive empirical results show the applicability and effectiveness of the proposed approach.

Ensembles of Evolved Nested Dichotomies for Classification - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2018, Kyoto, Japan, July 15-19, 2018)
In multinomial classification, reduction techniques are commonly used to decompose the original learning problem into several simpler problems. For example, by recursively bisecting the original set of classes, so-called nested dichotomies define a set of binary classification problems that are organized in the structure of a binary tree. In contrast to the existing one-shot heuristics for constructing nested dichotomies and motivated by recent work on algorithm configuration, we propose a genetic algorithm for optimizing the structure of such dichotomies. A key component of this approach is the proposed genetic representation that facilitates the application of standard genetic operators, while still supporting the exchange of partial solutions under recombination. We evaluate the approach in an extensive experimental study, showing that it yields classifiers with superior generalization performance.
Keywords: Classification; Hierarchical Decomposition; Indirect Encoding

Koopman Operator-Based Finite-Control-Set Model Predictive Control for Electrical Drives - Hanke, Sören; Peitz, Sebastian; Wallscheid, Oliver; Klus, Stefan; Böcker, Joachim; Dellnitz, Michael (arXiv:1804.00854)
Predictive control of power electronic systems always requires a suitable model of the plant. Using typical physics-based white box models, a trade-off between model complexity (i.e. accuracy) and computational burden has to be made. This is a challenging task with a lot of constraints, since the model order is directly linked to the number of system states. Even though white-box models show suitable performance in most cases, parasitic real-world effects often cannot be modeled satisfactorily with an expedient computational load. Hence, a Koopman operator-based model reduction technique is presented which directly links the control action to the system's outputs in a black-box fashion. The Koopman operator is a linear but infinite-dimensional operator describing the dynamics of observables of nonlinear autonomous dynamical systems which can be nicely applied to the switching principle of power electronic devices. Following this data-driven approach, the model order and the number of system states are decoupled which allows us to consider more complex systems. Extensive experimental tests with an automotive-type permanent magnet synchronous motor fed by an IGBT 2-level inverter prove the feasibility of the proposed modeling technique in a finite-set model predictive control application.